2009
DOI: 10.1002/hrm.20268
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of turnover intentions in learning‐driven and demand‐driven international assignments: The role of repatriation concerns, satisfaction with company support, and perceived career advancement opportunities

Abstract: International assignments have become an important part of managers' careers and are considered one of the most effective leadership development tools. Yet, studies consistently show that companies fail to integrate international assignments with long-term career development and succession planning and that a substantial percentage of expatriates leave the company upon completion of the international assignment. A total of 1,779 international assignees participated in a study that examined the factors associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
123
3
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(138 citation statements)
references
References 36 publications
7
123
3
5
Order By: Relevance
“…Although previous work is limited, the existing empirical evidence indicates that promotional or career advancement opportunities are related to various workrelated attitudes and behaviours, such as job satisfaction (Ellickson, 2002), turnover intentions (Stahl, Chua, Acliguiri, Cerdin, & Taniguchi, 2009), and job stress (Wickramasinghe, 2010;Yang, Che, & Spector, 2008). Further, consistent with social exchange theory and the norm of reciprocity, we speculate that promotional opportunities will enhance knowledge sharing behaviour because by doing so the employees can return the "favor" to the organisation.…”
Section: Perceived Promotional Opportunitiessupporting
confidence: 67%
“…Although previous work is limited, the existing empirical evidence indicates that promotional or career advancement opportunities are related to various workrelated attitudes and behaviours, such as job satisfaction (Ellickson, 2002), turnover intentions (Stahl, Chua, Acliguiri, Cerdin, & Taniguchi, 2009), and job stress (Wickramasinghe, 2010;Yang, Che, & Spector, 2008). Further, consistent with social exchange theory and the norm of reciprocity, we speculate that promotional opportunities will enhance knowledge sharing behaviour because by doing so the employees can return the "favor" to the organisation.…”
Section: Perceived Promotional Opportunitiessupporting
confidence: 67%
“…Overall, despite the growing importance of expatriation in various sectors, it is also seen as a 'double-edged sword' (Stahl, Chua, Caligiuri, Cerdin and Taniguchi 2009). Problems such as high turnover rates and increased psychosocial stress arise frequently.…”
Section: Expatriation: Challenges and Factors Influencing The Successmentioning
confidence: 98%
“…In support of this contention, Reiche, Kraimer, and Harzing (2011) found that expatriates who perceived fewer career prospects were more likely to leave their company two to four years later. Similarly, two other studies found that perceived opportunities for career advancement were negatively associated with repatriates' turnover intentions (Kraimer, Shaffer, & Bolino, 2009) and expatriates' turnover intentions (Stahl, Chua, Caligiuri, Cerdin, & Taniguchi, 2009). Although, to date, no empirical studies specifically link repatriate career satisfaction with retention, considerable evidence in domestic work has demonstrated the importance of career satisfaction on turnover intentions (e.g., Eddleston, 2009;Igbaria, 1991;Nauta, van Vianen, van der Heijden, van Dam, & Willemsen, 2009).…”
mentioning
confidence: 95%